The three burials of Melquiades Estrada - Jones, Tommy Lee, 1946-; Pepper, Barry, 1970-; Yoakam, Dwight; Jones, January (Culver City, Calif. : Sony Pictures Home Entertainment, 2006)
A rancher sets out to give his ranch hand and friend a proper burial after a border patrol guard has shot and buried the ranch hand.
Originally released as a motion picture in 2005.
Features: commentaries with Tommy Lee Jones, Dwight Yoakam, and January Jones, previews.
Tommy Lee Jones, Barry Pepper, Dwight Yoakam, January Jones.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
In English with optional English, French, or Spanish subtitles.
Keywords: Funeral rites and ceremonies -- Mexico -- Drama; Ranchers -- Drama; Video recordings for the hearing impaired; Feature films; Western films